Implementation of The STM32F407 Microcontroller Based 5-Level Inverter - Eko Yoyok Pujianti; Leonardus Heru Pratomo (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2022)
Technological developments continue to increase, this can be seen by the increasing number of electronic equipment used in daily needs, one of which is in the science of converting electrical energy, namely the 5-level inverter. The 5-stage inverter is a voltage changer that can convert DC electricity into AC electricity. Many studies have been carried out in order to obtain a sinusoidal 5-level inverter voltage waveform output by means of harmonic elimination technique. Harmonic elimination technique is a 5-level inverter signal processing technique for maximum switching patterns in order to obtain a sinusoidal output waveform and a minimum THD value with a combination of the STM32F407 microcontroller control signal generator circuit and the Mosfet Driver circuit, this 5-level inverter is expected to have a high output waveform. sinusoidal. testing is done with software in the form of PSIM software and real implementation. Based on the results, the method used is able to produce inverter output current and voltage with a THD of 4.38%.